Factors impacting decreased basic immunization coverage in infants: Risk of dangerous diseases - Meri Neherta; Lili Fajria; Prima Yoselina (Jurnal Keperawatan Padjadjaran, 2024)
Background: The data reveal a consistent decrease in the overall immunization coverage for babies in Kota Pariaman over a span of four years. Specifically, the coverage rates were recorded as 81.8% in 2018, 78.6% in 2019, 55.7% in 2020, and 66.7% in 2021. Purpose: The aim of this study is to identify the factors that contribute to the decrease in the achievement of complete basic immunization among children in Kota Pariaman. Methods: The present study used the quantitative research method with a cross-sectional design. The study sample comprised of mothers with infants aged 12 months residing in Pariaman City. A purposive sampling method was employed to choose a total of 154 participants. The research was carried out between March 2022 and October 2022. Univariate analysis describes variable frequency, bivariate examines relationships using chi-square (p<0.05) and multivariate employs logistic regression, identifying influential variables. Results: Key findings include a lack of knowledge (40.3%), non-supportive attitudes of mothers (56.5%), mistrust by mothers (42.9%), limited access to health resources (52.6%), and inadequate family support (48.1%). There was significant support from healthcare workers (94.2%) and moderate backing from community leaders (56.5%). Significantly, a noteworthy association was observed between knowledge (p < 0.05), attitudes (p < 0.05), and family support (p < 0.05), and the successful attainment of fundamental vaccinations. Conclusions: Factors leading to the decreased rate of complete basic immunization for infants in Kota Pariaman include attitude, family support, and knowledge. As a remedy, local governments and health workers are urged to proactively provide health education on the significance of full basic immunization for infants. This preventive measure is paramount in safeguarding against severe acute illnesses, benefiting both the child and the broader community